Prior exposure to stress delays extinction but does not modify reinstatement of nicotine-induced conditioned place preference - Leão, Rodrigo M [UNESP]; Cruz, Fábio C [UNESP]; Planeta, Cleopatra da Silva [UNESP] (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), 2010)
Studies in humans suggest that exposure to stress is related to relapse to tobacco use. The reinstatement of conditioned place preference (CPP) provides a simple, noninvasive and easy approach to investigate the mechanisms for drug relapse. The present study investigated whether repeated exposure to stress could change the extinction and reinstatement of nicotine-induced CPP. Adult male Wistar were exposed to restraint-stress for 2 hours/daily for 7 days, while the control-group was left undisturbed during this period. One day after the last stress session the CPP protocol was carried out. Nicotine produced a place preference to the compartment paired with its injections during conditioning (.16 mg/kg, s.c.; four drug sessions). Once established, nicotine place preference was extinguished by alternate exposure to each compartment after a saline injection (four exposures to each compartment). The animals that did not show extinction of CPP were submitted to two other extinction sessions. Following this extinction phase, the reinstatement of place conditioning was investigated following a priming injection of nicotine. Both control and stress groups showed reinstatement of CPP. The percentage of rats from the stress group that extinguished nicotine-CPP in the first and second test was lower as compared to the control group. In conclusion, stress delayed the extinction of the nicotine-induced CPP, but did not modify the reinstatement.